2012
DOI: 10.1039/c2gc35445d
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic C–N bond formation via simultaneous activation of C–H and N–H bonds: direct oxyamination of benzene to aniline

Abstract: † Electronic supplementary information (ESI) available: General procedures, catalyst characterizations and reaction data are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…By comparison, the two other hydrogels, tailored with a crosslinked PDMA frame, display much pronounced differences. As already described in previous papers, 20,22 the phase transition of short PNIPA chains anchored on the chemically crosslinked PDMA network starts at higher temperature (32-33 °C). This does not just have to do with the low molar mass of PNIPA grafts but it is also related to the penalty of selfassembling PNIPA chains covalently attached at one end to the PDMA network.…”
Section: Transition Temperature and Swelling Behaviorsupporting
confidence: 65%
See 2 more Smart Citations
“…By comparison, the two other hydrogels, tailored with a crosslinked PDMA frame, display much pronounced differences. As already described in previous papers, 20,22 the phase transition of short PNIPA chains anchored on the chemically crosslinked PDMA network starts at higher temperature (32-33 °C). This does not just have to do with the low molar mass of PNIPA grafts but it is also related to the penalty of selfassembling PNIPA chains covalently attached at one end to the PDMA network.…”
Section: Transition Temperature and Swelling Behaviorsupporting
confidence: 65%
“…After stirring overnight, almost full conversion was achieved, and polymers were purified by dialysis against pure water (membrane cut-off=50 kDa) during one week and recovered by freeze-drying. The syntheses of PDMA and PNIPA macromonomers were performed as previously described 22,23 using a telomerization process with cysteamine hydrochloride followed by modification of the amino end-group with acrylic acid in order to get the vinyl function. From previous works performed on similar systems, 24 it was shown that the functionalization of telomers with amino end-group is almost quantitative, at least greater than 90 %, as well as the subsequent vinyl modification of amino-end groups due to the large excess of activated…”
Section: Synthesis Of Linear Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Z. Zhuo et al reported that higher Lewis acidic strength of Ti active sites could promote the formation of NH 2 OH, 47 and NH 2 OH was thought as the reaction intermediate in ammoxidation benzene to aniline. 31,32,48 The formation of Ti-O-K might have negative impact on Ti site then the formation of NH 2 OH. If potassium was introduced rstly (the sample was named catalyst 2), the yield of aniline was only 0.14% with an extremely low selectivity of 9.7%, the XPS data of this sample indicated the formation of Ti-O-K species (data of characterisation of the catalyst were depicted in ESI †).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many researches on producing PTFE fiber with Poly(vinyl alcohol) (PVA) or Viscose as fiber-forming polymer through emulsion spinning technology. [9][10][11][12] Emulsion spinning technology involves spinning nascent fiber from mixture solution of PTFE dispersion and fiber-forming polymer, after which the fiber-forming polymer are removed by sintering process, and finally the PTFE fiber is obtained.…”
Section: Introductionmentioning
confidence: 99%